Velocity model estimated from seismic refraction survey and MASW, at Flamengos site (Faial island, Azores) - Neves, S. (2014)
The aim of this communication is to present the velocity models of propagation of seismic waves P and S using geophysical methods, such as refraction surveys and MASW (Multichannel analysis of surface waves). After determining the velocity models, the results were compared for the same location, with the lithology of the island. These results provide important physical parameters used for a near surface characterization of the soil structure and to predict seismic ground motion in this region.